Il valore del precedente giurisprudenziale in diritto romano e nella tradizione romanistica - Giovanni Luchetti (Vergentis. Revista de Investigación de la Cátedra Internacional Conjunta Inocencio III, 2018)
The aim of this study is to analyse, with a historical and legal perspective, the theme of the “jurisprudential precedent” in the Roman law, with the double perspective of the Science of Law and the judgements of the jurisdictional bodies, notwithstanding the observation of the fact that the responsa prudentium represent a source of production of law. The analysis will be carried out by offering a comparative overview both on the national legal systems between the 18th and the 19th century and on the current legal system of Common Law.